ANALISIS KONFLIK PERAN GANDA, KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN WANITA PADA PT. INDOMARCO PRISMATAMA PURWAKARTA - Dedeng Abdul Gani Amruloh (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
This study aims to determine whether there is Influence of Dual Role Conflict and Emotional Intelligence Against Employee Performance Women Office at PT. Indomarco Prismatama Purwakarta Branch. This research is quantitative research, research subject is employee women at office PT Indomarco Primatama Purwakarta Branch, data collection using questionnaires, sampling technique is a purposive sampling technique in which the researcher has certain criteria in the respondent's retrieval, while data analysis using multiple linear analysis. Multiple role conflict and emotional intelligence on employee performance at PT. Indomarco Prismatama Branch Purwakarta 56.7% and the remaining 43.3% influenced by other factors.